2005
DOI: 10.1093/eurheartj/ehi339
|View full text |Cite
|
Sign up to set email alerts
|

Complement component C5a predicts future cardiovascular events in patients with advanced atherosclerosis

Abstract: Complement activation, indicated by the elevation of C5a, seems to be associated with increased cardiovascular risk in patients with advanced atherosclerosis. Clinically, determination of C5a may add to the predictive value of other non-specific inflammatory parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
98
1
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(112 citation statements)
references
References 31 publications
8
98
1
5
Order By: Relevance
“…The extent of C5b-9 deposition appears to correlate with the severity of the lesion [49], with the greatest deposition of iC3b reported in vulnerable and ruptured plaques [49,50]. Indeed, elevations in circulating C5a levels have been associated with increased cardiovascular risk in patients with advanced atherosclerosis [51]. Results from the present study suggest that PMP can transport complement components to sites of vascular injury, and support local inflammation by supporting classical pathway complement activation.…”
Section: Discussionmentioning
confidence: 55%
“…The extent of C5b-9 deposition appears to correlate with the severity of the lesion [49], with the greatest deposition of iC3b reported in vulnerable and ruptured plaques [49,50]. Indeed, elevations in circulating C5a levels have been associated with increased cardiovascular risk in patients with advanced atherosclerosis [51]. Results from the present study suggest that PMP can transport complement components to sites of vascular injury, and support local inflammation by supporting classical pathway complement activation.…”
Section: Discussionmentioning
confidence: 55%
“…Thus, complement activation can contribute directly to local tissue destruction, inflammation, and atherogenesis. In this regard, Speidl et al (Speidl, Exner et al 2005) recently reported that plasma C5a levels were predictive of cardiovascular risk in patients with advanced atherosclerosis.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, iC3b deposition appears to be highest in vulnerable and ruptured plaques (Laine, Pentikainen, Wurzner, Penttila, Paavonen, Meri, and Kovanen 2002). Moreover, elevations in circulating C5a have been associated with increased cardiovascular risk in patients with advanced atherosclerosis (Seidl, Exner, Amighi, Kastl, Zorn, Maurer, Wagner, Huber, Minar, Wojta, and Schillinger 2005).…”
Section: Pathophysiology Of Platelet Mediated Complement Activationmentioning
confidence: 99%